Pengaruh Problem Solving terhadap Berpikir Kreatif di Moderasi Self-Regulated Learning - Oktariani, Mutiya (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
One of the essential elements of education for the twenty-first century that students must possess and develop is creative thinking. The purpose of this study was to ascertain how problem-solving techniques and self-regulated learning strategies combine to influence the capacity for creative thought. This study used a 2x3 factorial design and was quasi-experimental in nature. Questionnaires on self-regulated learning and tests of creative thinking were used to gather the data. Two-way ANOVA was used to analyze the data in SPSS Version 25. Based on the research that has been conducted argue that the effect of interaction between proble solving and self-regulated learning on creative thinking skill obtained F count value 13,763 with P = 0,000 < 0,05 it means that was and effect of the interaction between problem solving and self-regulated learning on creative thinking skill. Based on the result it was concluded that very effective in increasing creative thinking skill used problem solving and self-regulated learning.